Dislocation of the PIP-Joint - Treatment of a common (ball)sports injury - Müller-Seubert, Wibke; Bührer, Gregor; Horch, Raymund E. (Sportverletzung-Sportschaden, 2017)
Background Fractures or fracture dislocations of the proximal interphalangeal joint often occur during sports or accidents. Dislocations of the PIP-joint are the most common ligamentary injuries of the hand. As this kind of injury is so frequent, hand surgeons and other physicians should be aware of the correct treatment.Objectives This paper summarises the most common injury patterns and the correct treatment of PIP-joint dislocations.Materials and Methods This paper reviews the current literature and describes the standardised treatment of PIP-joint dislocations.Results What is most important is that reposition is anatomically correct, and this should be controlled by X-ray examination. Depending on the instability and possible combination with other injuries (e. g. injury to the palmar plate), early functional physiotherapy of the joint or a short immobilisation period is indicated.Conclusions Early functional treatment of the injured PIP-joint, initially using buddy taping, is important to restore PIP-joint movement and function. Depending on the injury, joint immobilisation using a K-wire may be indicated. Detailed informed consent is necessary to explain to the patient the severity of the injury and possible complications, such as chronic functional disorders or development of arthrosis.
EVALuna2:32840